Evaluation of mild encephalitis/encephalopathy with a reversible splenial lesion (MERS) by diffusion-weighted and diffusion tensor imaging. (4th June 2014) - Shankar, Balasubramanyam; Narayanan, Ramakrishna; Muralitharan, Pushkaran; Ulaganathan, Balamurugan
Abstract : Mild encephalitis/encephalopathy with a reversible splenial lesion (MERS) is a clinicoradiological entity with varied aetiologies and having a typical course of evolution. We present a case of MERS evaluated with diffusion-weighted and diffusion tensor imaging along with various conventional sequences of MRI. At the time of presentation, the lesions in the splenium of corpus callosum and bilateral cerebral white matter showed diffusion restriction with reduced apparent diffusion coefficient and no reduction in fractional anisotropy (FA) values on diffusion tensor imaging; on follow-up diffusion restriction completely resolved with normalisation of the apparent diffusion coefficient. The normal to slightly increased FA values in the lesions may indicate that MERS is a non-degenerative disorder.